Coverage disparities and delayed immunization: Assessing 12-month vaccination completion in Canadian children using data from a digital immunization platform - Mohamed Serhan; Adhiba Nilormi; Blaise Ntacyabukura; Katherine Atkinson; Robin Ducharme; Steven Hawken; Tim Ramsay; Joyce Ang; Kumanan Wilson (Human Vaccines & Immunotherapeutics)
On-time vaccination is essential for community protection against vaccine-preventable diseases. Insufficient on-time coverage and immunization series completion can put the population at risk. This study described individual coverage and series completion rates of the 12-month dose of pneumococcal, meningococcal, and measles-mumps-rubella (MMR) vaccines, as well as predictors of these rates in Canada. We conducted a cross-sectional study with immunization data from the pan-Canadian digital vaccination tool (CANImmunize) to evaluate coverage of the 12-month dose for single and multiple-dose vaccines. We conducted bivariate and multivariate logistic regression analyses to investigate associations between factors such as account holder gender, active integration of vaccine record with a public health unit (PHU) and inclusion of linked records in CANImmunize, with vaccination coverage. We calculated crude and adjusted odds ratios and 95% confidence intervals. We analyzed 60,890 records from children aged 13 months to 18 years. Coverage of the 12-month’s dose of multiple-dose vaccines was significantly lower compared to single-dose vaccines. 14.28% versus 17.23% of children who had reported the first dose of pneumococcal and meningococcal vaccines, respectively, have not received the 12-month dose of the same vaccine. Additionally, 10–13.2% of children who received the 12-month dose of pneumococcal, meningococcal, and MMR vaccines received the vaccine late (13+ months). Based on our data, there is a gap in the coverage of the 12-month dose between single and multiple-dose vaccines, and the 12-month dose was delayed for a proportion of children. Reminder interventions targeting populations with identified predictors of sub-optimal coverage may be valuable.